Leading Light: The Impact of Advanced Lighting Technologies on Indonesia's Office Industry - Murdiyansyah, Novan; Yandri, Erkata; Lodewijk, Dewi Putriani Yogosara; Ariati, Ratna (Leuser Journal of Environmental Studies, 2024)
Addressing concerns over resource scarcity and environmental sustainability necessitates a global shift towards sustainable energy, notably facilitated by adopting Light-Emitting Diode (LED) lamps. This transition is pivotal for ensuring global energy security and aligning with sustainability goals. This study endeavors to comprehensively analyze potential energy savings achievable through the transition from Fluorescent (FL) lamps to LED lamps within industrial offices. Emphasis is placed on highlighting the central role of energy efficiency. Utilizing false color rendering as a visual guide, the study systematically identifies areas where FL lamps inadequately illuminate. The findings prompt recalculations for determining optimal room illumination achievable through implementing LED lamps. Lux calculations are then employed to showcase the superior illumination offered by LED lamps, revealing consistent monthly cost savings of 35%, particularly when harmonized with Building Management System (BMS) control in industrial office buildings. The study's results indicate that LED lamps provide superior illumination, yielding a noteworthy 35% monthly cost savings, especially when integrated with BMS control. Lamps contribute modestly (21-30%) to overall energy consumption, while air conditioning commands a substantial 60%, underscoring the critical need for advanced lighting technology. This need is emphasized, particularly with Solar PV as a sustainable energy source. Understanding technological developments, especially in BMS, is crucial to optimize energy efficiency in industrial offices. The imperative implementation of LED lighting technology is a critical solution to address resource scarcity and environmental concerns in industrial offices. The efficacy of LED lamps in achieving significant energy savings, especially when coupled with advanced systems like BMS and complemented by renewable energy sources such as Solar PV. The conclusion stresses the significance of staying abreast of technological advancements to foster sustained progress towards energy-efficient and environmentally conscious practices within industrial environments.